2016
DOI: 10.1038/mp.2016.152
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor XBP1s restores hippocampal synaptic plasticity and memory by control of the Kalirin-7 pathway in Alzheimer model

Abstract: Neuronal network dysfunction and cognitive decline constitute the most prominent features of Alzheimer’s disease (AD), although mechanisms causing such impairments are yet to be determined. Here we report that virus-mediated delivery of the active spliced transcription factor X-Box binding protein 1s (XBP1s) in the hippocampus rescued spine density, synaptic plasticity and memory function in a mouse model of AD. XBP1s transcriptionally activated Kalirin-7 (Kal7), a protein that controls synaptic plasticity. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
93
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(100 citation statements)
references
References 66 publications
(92 reference statements)
5
93
0
1
Order By: Relevance
“…These observations suggest that BECN1 in the Central Nervous System (CNS) may be involved in the pathogenesis of neurodegenerative diseases. XBP1 was reported to protect against AD pathology; it was shown that transduction of hippocampus with sXBP1 rescued alterations in spine density, synaptic plasticity and memory loss in an AD mouse model (45). Several mechanisms for the amelioration of AD pathology by sXBP1 have been proposed; one such mechanism is the induction of disintegrin and metalloproteinase 10 (ADAM10) by sXBP1 (46).…”
Section: Xbp1 and Neurodegenerative Diseasesmentioning
confidence: 99%
“…These observations suggest that BECN1 in the Central Nervous System (CNS) may be involved in the pathogenesis of neurodegenerative diseases. XBP1 was reported to protect against AD pathology; it was shown that transduction of hippocampus with sXBP1 rescued alterations in spine density, synaptic plasticity and memory loss in an AD mouse model (45). Several mechanisms for the amelioration of AD pathology by sXBP1 have been proposed; one such mechanism is the induction of disintegrin and metalloproteinase 10 (ADAM10) by sXBP1 (46).…”
Section: Xbp1 and Neurodegenerative Diseasesmentioning
confidence: 99%
“…Thus, preserving the spines' dynamic and integrity is essential for the brain to develop synaptic networks capable of accurate information processing. Accordingly, tremendous efforts have been oriented toward therapeutic strategies aimed at circumventing Aβ neurotoxicity by activation of signaling pathways (13,19,20) that XBP1 exerts its beneficial effects in the brain through a regulatory loop involving IRE1α, XBP1 and BDNF. Generally consistent with the above findings, another study examined the role of XBP1 in the brains of naive mice and transgenic models of AD (19).…”
Section: Evidence For the Presence And Role Of Xbp1 In Dendritic Spinesmentioning
confidence: 99%
“…Accordingly, tremendous efforts have been oriented toward therapeutic strategies aimed at circumventing Aβ neurotoxicity by activation of signaling pathways (13,19,20) that XBP1 exerts its beneficial effects in the brain through a regulatory loop involving IRE1α, XBP1 and BDNF. Generally consistent with the above findings, another study examined the role of XBP1 in the brains of naive mice and transgenic models of AD (19). The report describes a preventive paradigm, as AD transgenic mice had no apparent synaptic and memory deficits at the time of intervention.…”
Section: Evidence For the Presence And Role Of Xbp1 In Dendritic Spinesmentioning
confidence: 99%
See 2 more Smart Citations